International handbook of practice-based performance management - Julnes, Patria de Lancer; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
A combination of conceptual and practical applications with an emphasis on cutting-edge practices in the US and abroad, this text represents the most notable examples of performance measurement in Canada, Latin America and Eastern Europe, and supports the integration of theory and practice, with linked chapters.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Government productivity; Administrative agencies -- Management; Administrative agencies -- Auditing; Nonprofit organizations -- Management; Organizational effectiveness; Total quality management; Performance -- Measurement; Electronic books